PREVENTIVE EFFECTS OF THE AQUEOUS EXTRACT OF CINNAMOMUM ZEYLANICUM BARK ON DEXAMETHASONE INDUCED INSULIN RESISTANCE IN WISTAR ALBINO RATS - CH, Rajasekhar; IM, Nagendranayak; B, Rajesh; B Nagraju, Kokila; N Banavasi, Guruprasad; Kumar V, Hemanth (International Journal of Clinical and Biomedical Research, 2015)
Objectives: To evaluate the preventive effects of aqueous extract of Cinnamomum zeylanicum bark on dexamethasone induced insulin resistance and to compare it with rosiglitazone. Methods: The animals were categorized into two series of dexamethasone (dexamethasone 4mg/kg, dexamethasone 8mg/kg series) with 5 groups in each [plain control, dexamethasone 4/8mg/kg as per series, rosiglitazone 8mg/kg and 16mg/kg, cinnamon bark extract (CZE) 250mg/kg BW]. Six animals were studied in each group. In a12 day study period, rosiglitazone and CZE groups received respective drug treatments and dexamethasone dosing (4mg/kg or 8mg/kg) was started from day 7onwards. On day 12, fasting blood, urine and post IPGTT blood samples were collected and processed for glucose, insulin and ketone estimations. Results: In both series, CZE 250mg/kg treatment showed significant reduction in mean fasting glucose and insulin compared to rosiglitazone 8mg/kg and 16mg/kg groups and dexamethasone controls (4mg/kg, 8mg/kg groups) (P<0.05). The fall in glucose and insulin levels observed with CZE treatment at 30, 60 min post IPGTT in both series were significant compared to rosiglitazone and dexamethasone treatment groups (P<0.05). Glycosuria and ketonuria were absent in CZE groups, whereas these were reduced significantly in rosiglitazone groups compared to dexamethasone groups (P<0.05). Conclusion: The aqueous extract of C. zeylanicum bark prevented the insulin resistance as evidenced by reduced fasting and post IPGTT glucose and insulin levels in steroid induced insulin resistance model. KEYWORDS: Glucose uptake; Cinnamon bark; Rosiglitazone; Hyperinsulinemia; Hyperglycemia.